Global e-VLBI observations of the gamma-ray narrow line Seyfert 1PMN J0948+0022 - Giroletti, M.; Paragi, Z.; Bignall, H.; Doi, A.; Foschini, L.; Gabányi, K. É.; Reynolds, C.; Blanchard, J.; Campbell, R. M.; Colomer, F.; Hong, X.; Kadler, M.; et al. (EDP Sciences, 2011)
Context: There is growing evidence of relativistic jets in radio-loud narrow-line Seyfert 1 (RL-NLS1) galaxies. Aims: We constrain the observational properties of the radio emission in the first RL-NLS1 galaxy ever detected in gamma-rays, PMN J0948+0022, i.e., its flux density and structure in both total intensity and polarization, its compactness, and variability. Methods: We performed three real-time e-VLBI observations of PMN J0948+0022 at 22 GHz, using a global array including telescopes in Europe, East Asia, and Australia. These are the first e-VLBI science observations ever carried out with a global array, reaching a maximum baseline length of 12 458 km. The observations were part of a large multiwavelength campaign in 2009. Results: The source is detected at all three epochs. The structure is dominated by a bright component, more compact than 55   μas, with a fainter component at a position angle θ ~ 35°. Relativistic beaming is required by the observed brightness temperature of 3.4 × 1011 K. Polarization is detected at a level of about 1%. Conclusions: The parameters derived by the VLBI observations, in addition to the broad-band properties, confirm that PMN J0948+0022 is similar to flat spectrum radio quasars. Global e-VLBI is a reliable and promising technique for future studies.